EVALUASI PROGRAM DAPUR SEHAT ATASI STUNTING (DASHAT) DENGAN PENINGKATAN STATUS GIZI DI WILAYAH KERJA PUSKESMAS MEDAN SUNGGAL - Damanik, Rani Kawati; Sipayung, Rosetti; Hutabarat, Tiara Slorinda Br (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
The evaluation of the implementation of DASHAT (Healthy Kitchen to Combat Stunting) is aimed at the cadres of TP-PKK, posyandu cadres, pregnant women, and mothers with toddlers. This research aims to examine the relationship between the evaluation of the Healthy Kitchen Program to Address Stunting (Dashat) and the improvement of nutritional status in the working area of the Medan Sunggal Community Health Center. The research method uses a descriptive correlational approach with a cross-sectional design. This study population of all mothers who have stunting children of 21 people this study sample uses Total Sampling technique. Data analysis using the Spearman test. The results of the research on the Evaluation of the Healthy Kitchen Program to Address Stunting (Dashat) indicate that the majority of the healthy kitchen programs have not been achieved, with 22 individuals (57.9%). The nutritional status in the working area of the Medan Sunggal Health Center is predominantly moderate, with 22 individuals (55.3%). There is a significant relationship between the evaluation of the healthy kitchen program to address stunting (Dashat) and the improvement of nutritional status, showing a significant correlation with a p-value of 0.000 (r = 0.560). Conclusion: The better the healthy kitchen program is implemented, the better the nutrition of children in the community will be. Suggestions are very important for promoting healthy eating habits and supporting initiatives aimed at improving nutrition in the community.